Efektivitas Edukasi Cairan dan Kulum Es Batu Pada Pasien Gagal Ginjal Kronik dengan Hemodialisis Terhadap Skala Haus dan Interdialytic Weight Gain di Rumah Sakit X Bogor - Hormat Janner Manurung; Ni Luh Widani; Sutanto Priyo Hastono (Malahayati Nursing Journal, 2023)
ABSTRACT Thirst and increased body weight between dialysis (IDWG) are the most common complaints of chronic kidney failure patients undergoing hemodialysis therapy. Possible complicationsnamely edema, shortness of breath, cardiopulmonary disorders. This research aims to determine the effectiveness of education on fluids and ice cubes in chronic kidney failure patients undergoing hemodialysis on the level of thirst and IDWG at Hospital X Bogor. Quasi-experimental research design pre and post test with the control group. Consecutive sampling consisted of 80 respondents, each group consisting of 40 respondents. Educational intervention on fluids and ice cubes 3 times a day for 2 weeks, in July-August 2022. Thirst level and IDWG measurements were carried out in the first week and fourth week. The results of univariate analysis of the majority of respondents on a moderate thirst scale (52.5%) and moderate level of IDWG (56%). The results of bivariate analysis with the marginal homogeneity test, t dependent test and independent t test There is a significant effect of thirst scale and IDWG before and after education on liquids and ice cubes with a p-value of 0.000; (p0.05). The results of the Ancova test multivariate analysis of the variables age, sex and duration of hemodialysis did not affect the level of thirst and IDWG with a p-value 0.05. There issignificant effect of fluid education and ice cube intervention simultaneously on the level of thirst and IDWG (p-values 0.000)after controlling for age, sex and duration of hemodialysis. This study recommends the need for education on fluids and ice cubes as an intervention in nursing care for chronic kidney failure undergoing hemodialysis therapy to avoid complications due to excess fluid. Keywords: Fluid Education, Ice Cube Cup, IDWG, Thirst Scale   ABSTRAK  Rasa haus dan peningkatan berat badan antar dialisis (IDWG) merupakan hal yang paling sering dikeluhkan pasien gagal ginjal kronik yang menjalani terapi hemodialisis. Komplikasi yang mungkin terjadi yaitu edema, sesak nafas, gangguan cardiopulmonary. Penelitian ini bertujuan mengetahui efektivitas edukasi cairan dan kulum es batu pasien gagal ginjal kronik yang menjalani hemodialisis terhadap tingkat haus dan IDWG di Rumah Sakit X Bogor. Desain penelitian Quasi Experimen pre dan post test dengan kelompok kontrol. Pengambilan sampel  consecutive sampling berjumlah 80 responden, masing-masing kelompok 40 responden. Intervensi edukasi cairan dan kulum es batu 3x sehari selama 2 minggu, pada Bulan Juli-Agustus 2022.   Pengukuran tingkat haus dan IDWG dilakukan pada minggu pertama dan minggu ke empat. Hasil analisis univariat mayoritas responden skala haus  sedang (52,5%) dan IDWG tingkat sedang (56 %). Hasil analisis bivariat dengan uji marginal homogeneity, uji t dependent dan uji t independent   Ada pengaruh signifikan skala haus dan IDWG sebelum dan sesudah edukasi cairan dan kulum es batu dengan  p- value 0,000 ; (p0,05). Hasil analisis multivariate  uji Ancova variabel usia, jenis kelamin dan lama hemodialisis tidak mempengaruhi tingkat haus dan IDWG dengan p- value 0,05.  Ada pengaruh yang signifikan edukasi cairan dan intervensi kulum es batu secara simultan terhadap tingkat haus dan IDWG (p- value 0,000) setelah dikontrol usia, jenis kelamin dan lama hemodialisis. Penelitian ini merekomendasikan perlunya   edukasi cairan dan kulum es batu sebagai salah satu intervensi dalam asuhan keperawatan gagal ginjal kronik yang menjalani terapi hemodialisis agar terhindar dari komplikasi akibat kelebihan cairan. Kata Kunci : Edukasi Cairan, IDWG, Kulum Es Batu, Skala Haus